Respostas agronômicas e ecofisiológicas da cultura da canola ao excesso hídrico - Tartaglia, Francilene de Lima (2016)
The objective of this study was to evaluate the agronomic and ecophysiological responses of canola cultivars grown under water excess in the soil, determining which crop stages are more sensitive, the length time of water excess tolerated and the tolerant cultivars. Four experiments were installed, two field and two in the greenhouse. Field experiments were conducted in two crop years (2014 and 2015), in Universidade Federal de Santa Maria, Santa Maria, RS, in a randomized block design, with split plot design, in a factorial 2 x 3, with factors drainage (with drain and no drain) and canola cultivars (Hyola 433, Hyola 411 and Hyola 61), with four replications. Were quantified plant height, number of leaves, leaf area, thermal time length of the development subperiods, leaf conductance, photosynthetic ratio and grain yield components. The experiments in greenhouse were conducted in Santa Maria and São Vicente do Sul, in 2015, in a factorial completely randomized design 4 x 5 in Santa Maria and with an additional treatment 5 x 4 + 1 in São Vicente do Sul, whose factors were phenological stages and time length with soil water excess (0, 24, 48, 96 and 192 h), with 3 replications. Were quantified the index of emergency velocity, emergency rate and yield components. The water excess in the soil causes morphological, phenological, physiological and productive changes in the canola crop. In the sowing-emergence subperiod, the soil water excess for a long time reduces the plant population. After the crop emergence, the rosette formation and onset of anthesis are the most critical stages to the canola crop. The plant population and the number of siliques per plant are the variables that most influence the productivity of canola grain in areas with water surplus. The use of drains is effective for the establishment and development of the canola in areas or periods with water excess. The length time that the canola crop supports water excess without reducing grain yield depends on the phenological stage, however, 24 h of water excess can reduce emergency velocity index, number of siliquas per plant, dry mass of shoots and grain yield. Productivity is most affected when the water excess occurs in the rosette formation and in onset of anthesis. There is a decreasing relationship between the increase in water surplus period and grain yield of the canola crop. The Hyola 411 and Hyola 433 cultivars may be promising for cultivation in areas with water excess. The Hyola 61 cultivar has productive potential, however, seems to be more sensitive to water excess in the soil.